A Rough Data Envelopment Analysis (RDEA) Model to Evaluate the Performance of Persian Language Satellite Networks Based on Youth Lifestyle Indicators - Shahin Mozaffari; Morteza Shafiee; Hamid Mahmoodian Ata Abadi (مطالعات رسانه‌های نوین, 2023)
Introduction